Consumer Support for a Maine Woods Tourism Quality Label - Vail, David; Daniel, Harold (Maine Policy Review, 2012)
David Vail and Harold Daniel report findings of a survey of North American vacationers. The survey assessed the strength of interest in quality-labeled Maine vacation experiences and tested consumer willingness to pay a price premium for certified tour “products.” The survey revealed that nearly four out of ten leisure travelers are responsive to the benefits promised by quality-labeled vacation experiences. The authors also describe steps communities, businesses, and state tourism leaders can take toward developing a Maine Woods quality label.